Physical conditioning programs for improving work outcomes among workers with back pain - Frederieke Schaafsma; Eva Schonstein; Anneli Ojajärvi; Jos Verbeek (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVES: The aim of this review was to assess the effect of physical conditioning programs, compared to no or alternative interventions, in reducing time lost from work among patients with back pain. METHODS: We conducted a systematic review with meta-analysis and meta-regression of randomized controlled trials (RCT) of physical conditioning programs for workers with back-pain-related work disability. RESULTS: We included 23 RCT with 3676 participants, with 13 studies having a low risk of bias. In 14 studies, physical conditioning programs were compared to "usual care". Among workers with acute back pain, there was no effect on sickness absence. For workers with subacute back pain, we found conflicting results. Among workers with chronic back pain, pooled results of five studies showed a small effect on sickness absence at one year follow-up [standardized mean difference (SMD) -0.18, 95% confidence interval (95% CI) -0.37-0.00] but this effect disappeared at longer follow-up times. Six studies compared physical conditioning programs to exercise only with conflicting results. The addition of cognitive behavioral therapy to physical conditioning programs did not change the effectiveness. The meta-regression showed no significant effect of program intensity, inclusion of a workplace visit, occupation, setting of the intervention, the type of comparison, or the follow up time. CONCLUSIONS: The effectiveness of physical conditioning programs in reducing sick leave for workers with back pain remains uncertain. For acute back pain, these programs probably have no effect; for subacute back pain, the effect is unclear, and for chronic back pain there is a small effect at one year follow-up that does not last in the long run. Remaining heterogeneity could not be explained by meta-regression. A better understanding of the mechanism behind physical conditioning programs and return to work is needed to develop more effective interventions